Persistence of leader cell behaviour can lead to malignant transformation in oral submucous fibrosis. (September 2022) - Sarode, Gargi S.; Sarode, Sachin C.; Sharma, Nilesh K.
Highlights: Due to coarseness and abrasive action, betel quid chewing causes micro-trauma to the oral mucosa. This stressor response leads to leader cell formation via activation of the p53-p21-CDK axis. Due to the chronic nature of the micro-trauma, there is persistence of leader cells. Continuous activation of the p53-p21-CDK axis can lead to malignant transformation. This type of leader cell malignancy could be a demographically and biologically distinct entity. Abstract: Betel quid (BQ) chewing-related oral submucous fibrosis (OSMF) is a common, potentially fatal condition in Southeast Asian countries. The literature has proved that BQ is associated with the development of micro-trauma-related injury to the oral mucosa. This is mainly attributed to the coarseness of the BQ and its abrasive action. Since, BQ chewing is a chronic habit in OSMF patients, it leads to the frequent development of micro-trauma and its repeated healing. This mechanism has been implicated in the pathogenesis of OSMF and its malignant transformation. However, the micro-trauma related mechanism for malignant transformation of OSMF is poorly understood. Leader cell formation is a well-known phenomenon in wound healing characterized by migration guidance to other cells, leading to epithelial repair. Due to repeated trauma and micro-wound formation in OSMF patients, we proposed the persistence of leader cells in the oral mucosa. This causes continuous activation of the p53-p21-CDK axis, which is an integral mechanism required for the transformation of normal epithelial cells into leader cells. We also propose that carcinogens derived from BQ chewing cause genetic and epigenetic changes in the leader cells. Overall, the persistence of leader cells in the oral epithelial population could be a major driver for malignant transformation in OSMF and a determinant of intra-tumoral heterogeneity. Strategies to curtail micro-trauma to the oral mucosa and target the leader cells hold good promise for preventing malignant transformation in OSMF.